Radio City Christmas spectacular [videorecording (DVD)] : starring the Rockettes. (Time Life Video, 2008)
This special 75th Anniversary DVD features all the best-loved performances of the Rockettes, including: The Dance of the Nutcracker, Parade of the Wooden Soldiers; Santa's Toy Headquarters, the Living Nativity and the arrival of Santa.